(untitled) (Training and Practice : Journal of Educational Sciences, 2011)
The first kindergarten by Friedrich Fröbel was founded in 1840. He became the greatest reformer of kindergarten education in the XIX. century by his pedagogical views focusing on the teaching of young children, recognizing the significance of play and establishing a specific kindergarten for children. Fröbel put the new kindergarten on specific metaphysical, antropological and historical- philosophical grounds. The idealistic image of children in the romanticism and the utopian view on history had a tremendernis effect on his work. He regarded the kindergarten as a Paradise given back to the children, where they should be saved and protected, and support, developing their divinity, were given. At the same time, according to Fröbel kindergarten also plays a significant role in renewing the life of adults and the arrival of a new age.